2017
DOI: 10.1016/j.apsb.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relationship between enteric-coated mycophenolate sodium dose and mycophenolic acid exposure in Han kidney transplantation recipients

Abstract: The aim of the research was to investigate the pharmacokinetics (PK) of enteric-coated mycophenolate sodium (EC-MPS) by quantification of the active metabolite of mycophenolic acid (MPA) after multiple escalating oral doses in Han kidney transplant recipients. A total of 28 Han postoperative kidney transplant recipients were given a multiple-dose of 540, 720 or 900 mg of EC-MPS two times a day in combination with tacrolimus for 6 days. Blood specimens were collected at each time point from 0 to 12 h after EC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Short-term stability at − 80 °C demonstrates that MPA and MPAG were stabled under this condition. Besides that, it has already been described in the literature that samples are stable in plasma at − 80 °C for at least 6 months, so kidneytransplanted samples were kept at this condition until analysis [10,13,19,24].…”
Section: Bioanalytical Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Short-term stability at − 80 °C demonstrates that MPA and MPAG were stabled under this condition. Besides that, it has already been described in the literature that samples are stable in plasma at − 80 °C for at least 6 months, so kidneytransplanted samples were kept at this condition until analysis [10,13,19,24].…”
Section: Bioanalytical Methods Validationmentioning
confidence: 99%
“…In this study, to determinate and oral fluid concentrations of MPA and MPAG, the validated LC-MS method was applied to samples from 13 kidney transplant patients. To analyse the results, a non-compartmental model was used as it has already been described for MPA and MPAG in several studies [17,19,[25][26][27]. The plasma and oral fluid concentrations of MPA and MPAG were found to be variable for both analytes (Fig.…”
Section: Pharmacokinetics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The blood samples were centrifuged at 3000 r/min and plasma samples were separated. MPA concentrations were analyzed using the validated ultra-performance liquid chromatography ultraviolet (UPLC-UV) method ( Zhang et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of the quality of interactions of the 10 best compounds revealed that Simeprevir had the highest number of polar bonds with side chains of residues in the RBD binding pocket. Simeprevir, a second-generation HCV NS3/4A protease inhibitor 28 , has been reported to be both a SARS-CoV-2 main protease inhibitor 29 and a S protein-RBD interaction inhibitor 30 . Simeprevir forms an extended network of H-bonds with Arg403, Lys417, Gln493, Gly496 and Tyr505, and forms Van Der Waals interactions with Tyr421, Tyr453 and Tyr505 (Fig.…”
Section: Resultsmentioning
confidence: 99%